Study of the Application of the RCA and Six Sigma Method for Quality of the Kalimas River in Surabaya (Prestasi Park-Petekan Bridge Segment) - Ino Tri Wulansari; Nieke Karnaningroem (Institut Teknologi Sepuluh Nopember, 2019)
Kalimas River is a water body that passes through the city of Surabaya. The study was conducted on the Kalimas River (Segment of the Bridge Achievement Bridge) with a length of approximately 6 km. Based on the results of the water quality test of the Kalimas River (Prestasi Park-Petekan Bridge Segment) in 2016, it was found that there were several parameters that did not meet the class II water quality standards, namely BOD, COD, DO, TSS, and Phosphate. According to the Surabaya City Regulation2014-2034, the Kalimas River will be used as atourist spot and river transportation service center, so the river water must meet the quality standards for water recreation areas, which is Class II water quality.Due to these problems, the research on controlling water quality is very important. This study uses the Six Sigma method with DMAIC concept. Six Sigma is a continuous improvement effort to determine variations in the process, in order to improve the capability of that process in producing products and minimizing defects. As a characteristic of Six Sigma, DMAIC consists of five stages, which are define–measure–analyze–improve–control. Some parameters that will be used are BOD, COD, DO, TSS, pH, nitrogen, phosphateand total coliform. The first stage is “define”,in which the water quality of the Kalimas River will be measured in the form of BOD, COD, DO, TSS, pH, Nitrogen and Phosphate. Then the “measure” stage will be calculated as Deffect per Million Opportunities (DPMO) and sigma levels. In the “analyze” stage, the Root Cause Analysis (RCA) method is used to determine the root of the problem. “Improve” stage will determine potential solutions or action plans that can be applied. Then the “control” stage is conducted by making a plan to control the implementation of the action plan. The results of analysis at the six points show that there are several parameters that do not meet the Class II water quality standards, namely DO, BOD, COD, TSS, phosphate and total coliform. After calculating the Deffect per Million Opportunities in the“measure”stage, the value of the sigma level is 2.75. In the“analyze”stage, RCA method was used to find the root cause of the Kalimas River (Prestasi Park-Petekan Bridge Segment), and found the root cause was the inclusion of wastewater into rivers and river management systems